INVESTIGATION OF THE STRUCTURE OF ALSI25CU4CR AND ALSI25CU5CR ALLOYS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The hypereutectic aluminium-silicon alloys AlSi25Cu4Cr and AlSi25Cu5Cr are heat treated T5, T6 and T7. The quenching of the alloys was carried out under the same conditions. Artificial aging at T5 was carried out at a temperature of 180º C for 2, 4 and 6h, and at T6 at 180º C for 8, 10, 12 and 14h. The artificial aging of the studied compositions at T7 was carried out at a temperature of 370º C for 20, 40 and 60 min. The influence of heat treatment on the size, shape and distribution of primary and eutectic silicon crystals in the alloy structure was investigated. It was established that the proposed heat treatment regimes do not lead to a significant change in the shape and size of the primary silicon crystals, but contribute to their uniform distribution in the structure of the studied alloys. Rounding of the silicon crystals in the composition of the eutectic of the investigated alloys was observed.